Azole antifungals: 35 years of invasive fungal infection management. Issue 6 (June 2015) - Allen, David; Wilson, Dustin; Drew, Richard; Perfect, John
<x xml:space="preserve">Abstract</x> Prior to 1981, treatment options for invasive fungal infections were limited and associated with significant toxicities. The introduction of ketoconazole marked the beginning of an era of dramatic improvements over previous therapies for non–life-threatening mycosis. After nearly a decade of use, ketoconazole was quickly replaced by the triazoles fluconazole and itraconazole due to significant improvements in pharmacokinetic profile, spectrum of activity and safety. The triazoles posaconazole and voriconazole followed, and were better known for their further extended spectrum, specifically against emerging mold infections. With the exception of fluconazole, the triazoles have been plagued with significant inter- and intrapatient pharmacokinetic variability and all possess significant drug interactions. Azoles currently in development appear to combine an in vitro spectrum of activity comparable to voriconazole and posaconazole with more predictable pharmacokinetics and fewer adverse effects.